The Importance of Mentoring for the Professional Career of Heads of Preschool Education Institutions - Makutėnė, Aida (Jaunųjų mokslininkų darbai, 2025)
The article actualizes the role of the head of an educational institution, analyzes the influence of the relationship between a professional mentor and a student on the professional career of the head of a preschool educational institution. It emphasizes how mentoring significantly contributes to developing the leadership of heads, strengthening professional competencies, motivating them to develop a professional career, growing potential, and training a head of an educational institution who is creating a sustainable future on their professional path.